The impact of loneliness on late-life depression and anxiety during the COVID-19 pandemic - Müller, Julia; Elsaeßer, Moritz; Berger, Ruben; Müller, Wiebke; Hellmich, Martin; Zehender, Nadine; RiedelHeller, Steffi; Bewernick, Bettina H; Wagner, Michael; Frölich, Lutz; Peters, Oliver; Domschke, Katharina; et al. (American journal of geriatric psychiatry, 2025)
Objective - This study investigates the association of loneliness during the COVID-19 pandemic and the course of depressive, anxiety and sleep symptoms after psychological treatment in older adults. - Methods - During the first wave of the pandemic in 2020, we assessed additional, original data of 132 participants aged ≥60 years who had completed psychological treatment for late-life depression (LLD) in the context of a multicenter, randomized controlled trial (CBT-late). We measured loneliness using the UCLA Loneliness Scale. Depression, anxiety and sleep symptoms were assessed using the Geriatric Depression Scale (GDS), Geriatric Anxiety Inventory (GAI), and Insomnia Severity Index (ISI). - Results - Participants with higher loneliness scores (n = 44) experienced a significant worsening of depressive and anxiety symptoms during the pandemic (estimated marginal mean difference (emmd) of change in GDS between post-treatment and COVID-19 visit: GDSemmd= −4.61, [95% CI: −6.97 to −2.26], GAIemmd= −2.21, [95% CI: −3.76 to −0.65]), while those with low to moderate loneliness (n = 72) maintained stable mild symptoms (GDSemmd= −1.39, [95% CI: −3.00 to 0.22], GAIemmd= −0.49, [95% CI: −1.69 to 0.72]). All patients reported increased sleep disturbances during the pandemic regardless of loneliness, while remaining in the range for sub-threshold insomnia. - Conclusions - Our results suggest an association of significant loneliness during the COVID-19 pandemic and a clinically relevant worsening of depressive and anxiety symptoms in older adults. Loneliness assessments and interventions may be incorporated into treatments for LLD, particularly during pandemics or other crises.